Evaluation of soluble transferring receptor levels in children with iron deficiency and beta thalassemia trait, and in newborns and their mothers - Polat, Aziz; Kaptanoğlu, Bünyamin; Aydın, Kemal; Keskin, Ali (The Turkish Journal of Pediatrics, 2002)
In this study we first aimed to investigate the value of soluble transferrin receptor levels (sTfR) in healthy, iron deficient and beta thalassemia trait children and to determine whether sTfR is a useful indicator of iron deficiency. Secondly, we investigated the effects of iron supplementation of sTfR levels in a group of iron deficient children. Third was to describe sTfR in newborn infants and determine whether or not maternal iron deficiency is an important predictor of infant sTfR. Six groups were formed: Children with iron deficiency (n=22), post-iron therapy (n=16), beta thalassemia traits (n=19), healthy children (n=19), full-term newborns (n=20), and their mothers (n=19), Complete blood count (CBC), serum iron, iron-binding capacity, ferritin and sTfR levels were measured. sTfR/log ferritin indexes were calculated. sTfR levels of children with iron deficiency and with beta thalassemia trait were found to be significantly higher than those of healthy children (p<0.0001 and p<0.001). Children with iron deficiency showed a greater increase in the levels of sTfR than those with beta thalassemia traits (p=0.008). Although sTfR levels of subjects having iron therapy decreased, the levels still remained high compared to controls (p=0.002). Newborns had significantly higher levels of sTfR than controls (p<0.0001). Although sTfR levels of mothers with iron deficiency were higher than those of mothers having no iron deficiency (p=0.009), there was no difference in the levels of sTfR between newborns of both groups of mothers (p=0.790). sTfR is a useful parameter which shows body iron status as well as erythropoietic activity in children. It is independent of mother’s iron status, and is due to erythropoietic activity in newborns.